2019
DOI: 10.1248/cpb.c18-00752
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Drug Crystallization by Cyclodextrins in Pre-formulation Study

Abstract: Controlling drug crystallization is one of the important issues in pre-formulation study. In recent years, advanced approaches including the use of tailor-made additives have gathered considerable attention to control crystallization behavior of drugs. This review focuses on the use of hydrophilic cyclodextrins (CDs) as additives for controlling drug crystallization. CDs affect the crystallization of drugs in solution and in solid state based on a host-guest interaction. For example, 2,6-di-O-methyl-β-CD and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
3
0
1
Order By: Relevance
“…Aprotinin (a small protein with a molecular weight of 6500 Da) is a competitive enzyme inhibitor of several serine proteases, such as trypsin and chymotrypsin [108]. It has been used as an enzyme inhibitor in various studies investigating protein and peptide drug absorption across Citric acid Insulin [96,97] Cyclodextrins Limaprost [98] Glycerides DuP 532 [99] Lauroyl carnitine chloride Insulin [100] Sodium lauryl sulfate (SLS/sodium dodecyl sulfate) Cefazolin [101] Sodium N-[8-(2-hydroxybenzoyl) aminocaprylate] Semaglutide [102] the intestinal membrane. One study has revealed that insulin-containing microemulsions concomitantly orally administered with aprotinin, compared with those without aprotinin, significantly decrease plasma glucose levels between 90-120 min after administration in both nondiabetic and diabetic rat models [109].…”
Section: Enzymatic Inhibitorsmentioning
confidence: 99%
“…Aprotinin (a small protein with a molecular weight of 6500 Da) is a competitive enzyme inhibitor of several serine proteases, such as trypsin and chymotrypsin [108]. It has been used as an enzyme inhibitor in various studies investigating protein and peptide drug absorption across Citric acid Insulin [96,97] Cyclodextrins Limaprost [98] Glycerides DuP 532 [99] Lauroyl carnitine chloride Insulin [100] Sodium lauryl sulfate (SLS/sodium dodecyl sulfate) Cefazolin [101] Sodium N-[8-(2-hydroxybenzoyl) aminocaprylate] Semaglutide [102] the intestinal membrane. One study has revealed that insulin-containing microemulsions concomitantly orally administered with aprotinin, compared with those without aprotinin, significantly decrease plasma glucose levels between 90-120 min after administration in both nondiabetic and diabetic rat models [109].…”
Section: Enzymatic Inhibitorsmentioning
confidence: 99%
“…The polymorph control on drug crystals is a primary concern in pharmaceutics because the morphology differences lead to direct variances in drug efficacy. Therefore, the preceding reports on the polymorphism of CD-containing crystals are exclusively for their inclusion complexes, while no polymorphism has hitherto been reported for uncomplexed native CDs. When native CDs spontaneously crystallize in aqueous solution, several water molecules are incorporated inside and outside the CD cavity. ,, For β-CD, the crystal structure with variable hydration water molecules ranging from 9.4 to 12.3, i.e ., β-CD·(9.4–12.3)­H 2 O, has already been identified .…”
Section: Introductionmentioning
confidence: 99%
“…Crystallization has been a topic of research due to its key role in geochemistry, biology, and synthetic materials, which are extensively applied in the chemical, pharmaceutical, and food sectors [1][2][3] . Especially in the pharmaceutical sector, 90% of the goods are crystalline organic compounds that require refinement through recrystallization procedures 4,5) .…”
Section: Introductionmentioning
confidence: 99%